2013
DOI: 10.1148/radiol.12112789
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Perfused Blood Volume with Dual-Energy CT as Surrogate for Pulmonary Perfusion Assessed with Dynamic Multidetector CT

Abstract: CT-derived PBV heterogeneity is a suitable surrogate for CT-derived PBF heterogeneity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
100
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 19 publications
3
100
1
8
Order By: Relevance
“…The average HU enhancement of 34 HU in this study is similar to the work of Groell et al , which observed an enhancement of 30 HU in the normal lung segment by comparing precontrast and postcontrast CT scans 37 . Also the 13–20 s delay time between contrast administration and CT image acquisition in this study is similar to other CT perfusion studies, e.g., 13 s by Wildberger et al 12 and 15 s by Fuld et al , 38 Given that this study included dogs with varying breeds (e.g., Pembroke Welsh Corgi and Shepherd), weight (range 13.1–42.5 kg), and lung pathologies (normal, primary lung tumor, lung metastasis, or interstitial lung disease), there might be intersubject variability in the hemodynamic profile, which could influence the optimal delay time. Optimizing the delay time using a more specific patient population would be an important subject of future work.…”
Section: Discussionsupporting
confidence: 90%
“…The average HU enhancement of 34 HU in this study is similar to the work of Groell et al , which observed an enhancement of 30 HU in the normal lung segment by comparing precontrast and postcontrast CT scans 37 . Also the 13–20 s delay time between contrast administration and CT image acquisition in this study is similar to other CT perfusion studies, e.g., 13 s by Wildberger et al 12 and 15 s by Fuld et al , 38 Given that this study included dogs with varying breeds (e.g., Pembroke Welsh Corgi and Shepherd), weight (range 13.1–42.5 kg), and lung pathologies (normal, primary lung tumor, lung metastasis, or interstitial lung disease), there might be intersubject variability in the hemodynamic profile, which could influence the optimal delay time. Optimizing the delay time using a more specific patient population would be an important subject of future work.…”
Section: Discussionsupporting
confidence: 90%
“…Whether this phenomenon exists in patients with ALI remains speculative, but it was previously observed in healthy people during exercise (33). Interestingly, the same excellent correlation (R 2 5 0.84) between blood flow and blood volume was recently found in anesthetized, mechanically ventilated pigs (34). A weaker, although significant, correlation between lung perfusion and pulmonary blood volume (R 2 5 0.50) assessed with MR imaging was also found in 23 patients (35).…”
Section: Discussionmentioning
confidence: 53%
“…Noteworthy, the r value and slope obtained in this study are comparable to those calculated by Schuster et al [6] ( r  = 0.77, slope = 0.92) and Richard et al [9] ( r  = 0.79, slope = 0.79) using PET and 15 O-labeled water. Unfortunately, there is no PBF obtained by CT to compare with our results [26, 27]. …”
Section: Discussionmentioning
confidence: 79%
“…This is even more important due to the fact that these agents, either linear or macrocyclic, are under investigation for multiple results demonstrating their potential accumulation in various tissues regardless of renal function [25]. Our alternative has a simpler implementation and provides quantitative measures of the regional blood flow compared to recent approaches using dual energy CT imaging [26, 27]. Compared to other PET-based alternatives such as 15 O-water [7] or dissolved 13 N 2 [28] that need an on-site cyclotron, our solution could be potentially more widely available due to the introduction of gallium generators in the field and the approval of different gallium-chelated agents for human use.…”
Section: Discussionmentioning
confidence: 99%